2023
DOI: 10.1080/19490976.2023.2190301
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of associations between gut microbiota composition and growth failure in preterm neonates

Abstract: Growth failure is among the most prevalent and devastating consequences of prematurity. Up to half of all extremely preterm neonates struggle to grow despite modern nutrition practices. Although elegant preclinical models suggest causal roles for the gut microbiome, these insights have not yet translated into biomarkers that identify at-risk neonates or therapies that prevent or treat growth failure. This systematic review aims to identify features of the neonatal gut microbiota that are positively or negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…Interestingly, we found that the relative abundance of Staphylococcus was negatively correlated with bodyweight gain, consistent with previous results by Aguilar-Lopez et al [35]. Yet, a recent meta-analysis could not confirm a consistent link between Staphylococcus abundance and bodyweight gain [44], and the significance of these findings for BC-fortified VPIs remains to be clarified.…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, we found that the relative abundance of Staphylococcus was negatively correlated with bodyweight gain, consistent with previous results by Aguilar-Lopez et al [35]. Yet, a recent meta-analysis could not confirm a consistent link between Staphylococcus abundance and bodyweight gain [44], and the significance of these findings for BC-fortified VPIs remains to be clarified.…”
Section: Discussionsupporting
confidence: 90%
“…This process favors adequate colonization by harmless microorganisms that protect a newborn from pathogens. Adequate and diverse colonization positively influences the immune, metabolic, cognitive, and sensory development of a newborn [ 16 , 17 , 18 ]. The intestinal microbiota of a newborn is very simple at birth and is influenced by the type of delivery, the use of antibiotics, or the type of diet, with the MOM being one of the first sources of bacteria.…”
Section: Introductionmentioning
confidence: 99%